2020
DOI: 10.3390/d12030112
|View full text |Cite
|
Sign up to set email alerts
|

Plant Invasion Has Limited Impact on Soil Microbial α-Diversity: A Meta-Analysis

Abstract: Plant invasion has proven to be a significant driver of ecosystem change, and with the increased probability of invasion due to globalization, agricultural practices and other anthropogenic causes, it is crucial to understand its impact across multiple trophic levels. With strong linkages between above and belowground processes, the response of soil microorganisms to plant invasion is the next logical step in developing our conceptual understanding of this complex system. In our study, we utilized a meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Our observation that microbial richness and Shannon diversity did not differ between monoculture and polyculture plots is not surprising because microbial diversity metrics, in general, are not reliable indicators of ecological processes (Shade, 2017). For example, the effects of invasive plant species on soil are well documented, but microbial community richness is rarely significantly affected (Custer & van Diepen, 2020). In our study, plant diversity could be acting on the functions and activity of soil microbial communities, but such impacts might not be reflected in richness metrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that microbial richness and Shannon diversity did not differ between monoculture and polyculture plots is not surprising because microbial diversity metrics, in general, are not reliable indicators of ecological processes (Shade, 2017). For example, the effects of invasive plant species on soil are well documented, but microbial community richness is rarely significantly affected (Custer & van Diepen, 2020). In our study, plant diversity could be acting on the functions and activity of soil microbial communities, but such impacts might not be reflected in richness metrics.…”
Section: Discussionmentioning
confidence: 99%
“…These results are more unexpected than the diversity results because it is generally assumed that intervention above‐ground during restoration cascades below‐ground (Kardol & Wardle, 2010). For example, during plant invasion, invaded areas tend to have different soil microbial community composition than treated or uninvaded areas (Custer & van Diepen, 2020; Gornish et al., 2020; Parsons et al., 2019). However, robust tests of the relationship between restoration treatments and soil microbial communities across different sites are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The stable microbial diversity indices in the constructed wetland might be because of the compensation from other microbial groups for some microbial variations or the limited impacts of plant invasion on microbial α diversity indices (Custer and van Diepen, 2020). The result of LEfSe showed that the microbial community structure in the river and the constructed wetland was significantly different between the invaded and non-invaded sites (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…These alterations can have effects on not only mycorrhizal fungi but also free-living fungi and bacteria, which play a key role in determining resource availability and consequently the structure and composition of plant communities (Torres et al, 2021;Zhang et al, 2019). However, our limited understanding of the microbial communities' response to invasion is due to microbial diversity being strongly dependent on specific site characteristics and edaphic factors (Custer & van Diepen, 2020). Many studies which have recorded the effects of invasive plants on the soil microbial community have found that the direction and strength of the effects are entirely circumstantial (Callaway et al, 2004;Kourtev et al, 2003;Zhang et al, 2019).…”
Section: Effects Of Invasive Species On the Microbial Communitymentioning
confidence: 99%
“…to gain generalised effects of plant invasion on the soil microbial community largely reduces our ability to fully understand the effects of invasive plants. Both bacteria and fungi play important roles in the functioning of ecosystems, therefore understanding their responses to plant invasion, which is likely to become a greater threat in the future, is crucial (Custer & van Diepen, 2020).…”
Section: Effects Of Invasive Species On the Microbial Communitymentioning
confidence: 99%